Neurofilament light as a biomarker for motor decline in Parkinson’s disease - Liu, Yumei; Dou, Kaixin; Xue, Ling; Li, Xiaoyuan; Xie, Anmu (Frontiers in Neuroscience, 2022)
Objectives The aim of this study was to determine whether neurofifilament light (NfL) could reflect motor decline and compare the predictive values of cerebrospinal fluid (CSF) and serum NfL in individuals with PD. Methods CSF/serum samples were collected from patients with PD and healthy controls (HCs) with motor assessments at baseline and after three years of follow-up from the Parkinson’s Progression Markers Initiative (PPMI). Multiple linear regression models and linear mixed-effects models were used to investigate the associations of motor assessments with baseline and longitudinal CSF/serum NfL. Associations between the change rates of motor assessments and CSF/serum NfL were further investigated via multiple linear regression models. Mediating effect analysis was used to research whether CSF alpha-synuclein (α-syn) acts as the mediator between NfL and motor assessments. Results We found patients with PD had higher baseline CSF/serum NfL levels than HCs. Both baseline CSF/serum NfLs and their change rates predicted measurable motor decline in PD assessed by different motor scores. Baseline serum NfL and its rate of change were strongly associated with CSF NfL levels in patients with PD (P < 0.001). Besides, there were also significant differences in CSF/serum NfL levels and predicted values of motor decline between men and women with PD. Mediating effect analysis showed CSF α-syn mediated the effect of CSF NfL on total Unified Parkinson’s Disease Rating Scale (UPDRS) scores and UPDRSIII with 30.6 and 20.2% mediation, respectively. Conclusion Our results indicated that NfL, especially serum NfL concentration, could serve as an easily accessible biomarker to monitor the severity and progression of motor decline in individuals with PD, especially in men with PD. Besides, CSF α-syn acts as a mediator between NfL and motor progression.